Improved clustering algorithm based on energy consumption in wireless sensor networks. Issue 3 (1st May 2017) - Wu, Wenliang; Xiong, Naixue; Wu, Chunxue
Abstract : Wireless sensor networks (WSNs) are widely used in military, traffic, medical and so on. The design of routing protocol for WSNs is limited by the single nature of the local topology information. Meanwhile, the power supply of sensor networks node, communication ability and storage capacity are limited, so how to improve the efficient energy of nodes and extend the networks life cycle is the focus of current research. This study proposes the improved algorithm for the LEACH (Low Energy Adaptive Clustering Hierarchy) clustering algorithm, considering the residual energy of the nodes and the factors of the long distance node, the T ( n ) is readjusted and the new method is proposed. Then the data fusion rate is introduced to allow the cluster‐heads to fuse data before sending the data, and send the data to the base station. Finally, the free‐space model and the multi‐path fading model are adopted to avoid the excessive consumption of energy caused by the node d 4 . The authors' simulation results show that the improved algorithm can reduce the energy consumption of the networks and prolongs life cycle.